2020
DOI: 10.1155/2020/7323521
|View full text |Cite
|
Sign up to set email alerts
|

A Clean and Sustainable Cellulose‐Based Composite Film Reinforced with Waste Plastic Polyethylene Terephthalate

Abstract: With the widespread use and increasing consumption of PET, the amount of waste PET is growing rapidly, and the accompanied environmental problems will become more and more serious. Therefore, the recycling and reuse of PET are of great significance for not only saving resources but also solving environmental issues. In this study, Methylcellulose (MC) composites reinforced with waste plastics polyethylene terephthalate (PET) were prepared by casting an MC/PET solution with a varying mass ratio of MC to PET. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Figure gives the XRD patterns of selected samples. MC displays two characteristic diffractions of the semicrystalline structure at 2θ = 8.9 and 19.7°. , PMMA exhibits an amorphous structure with two broad diffraction peaks at around 2θ values of 15 and 30°. , In the XRD patterns of the PMMA/MC films, the diffraction signal for MC at 8.9° is absent, and the intensity of the diffraction signal at 19.7° is decreased. At the same time, the intensity of the diffraction signal at 19.7° for MC becomes weaker with an increase in the amount of PMMA in proportion to MC.…”
Section: Resultsmentioning
confidence: 95%
“…Figure gives the XRD patterns of selected samples. MC displays two characteristic diffractions of the semicrystalline structure at 2θ = 8.9 and 19.7°. , PMMA exhibits an amorphous structure with two broad diffraction peaks at around 2θ values of 15 and 30°. , In the XRD patterns of the PMMA/MC films, the diffraction signal for MC at 8.9° is absent, and the intensity of the diffraction signal at 19.7° is decreased. At the same time, the intensity of the diffraction signal at 19.7° for MC becomes weaker with an increase in the amount of PMMA in proportion to MC.…”
Section: Resultsmentioning
confidence: 95%
“…The authors showed that ultra-fine PET nanofibers were successfully manufactured from plastic bottles for application as face masks or air filters [270]. The use of PET waste in adequate proportions to obtain composites can improve some properties [271]. Recently, Aydogmus et al [272], produced a biocomposite reinforced with polyethylene terephthalate waste, and it was observed that the behavior of the biocomposite at high temperatures improved with increasing PET waste content.…”
Section: Polymeric Composites For Waste Recoverymentioning
confidence: 99%
“…Sustainability necessitates the advancement of human science and technology, as well as a greater demand for trees, [ 12 , 13 , 14 ] plants, some marine organisms, and algae having a fundamental reinforcing property that enhances all subsequent constructions. The bulk of the hierarchical structure is eliminated by extracting cellulose at the nanoscale, and a new cellulose-based “building block” is available as composites [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%